Used Textiles and the Basel Convention - Environmental Justice and the Influence of the European Union - Björkman,Hilda (2025)
More than one million tonnes of used textiles are exported from the European Union (EU) every year, often to the Global South. Used textiles are exported for reuse in the interests of circularity and extending the lifetime of a product on a secondary market. Nonetheless, substantial portions of the exported textiles are not fit for reuse. In these instances, such textiles often end up in informal waste streams. This causes adverse environmental effects in the importing country and disfavours environmental justice. Despite the associated environmental harm, the used textile trade is largely unregulated by international environmental law (IEL). The EU has made efforts to fill this regulatory gap. At the regional level, the EU has adopted strict regulations concerning the used textile trade in Regulation 2024/1157, the Waste Shipment Regulation (WSR). The EU has also expressed interest in setting the agenda at the international level. In 2024, the Danish, French and Swedish delegations suggested a common EU proposal for an amendment to the Basel Convention on the Control of Transboundary Movements of Hazardous Wastes and their Disposal. The amendment would subject textile waste to the control mechanisms of the Convention. At the seventeenth meeting of the Conference of the Parties (COP) to the Basel Convention in May 2025, the COP initiated a new area of work related to addressing transboundary movements of textile wastes. The aim of this thesis is to explore the potential added value to IEL of an amendment to include textiles in the category of wastes controlled by the Basel Convention. In the thesis, I analyse the Basel regime and conclude that the Basel Convention currently addresses textile wastes only to a minimal extent. The inadequate international regulatory order has facilitated the evolution of a global used textile trade that goes beyond the inspection radar of customs authorities and harms the environment. I argue that an amendment to the Basel Convention regarding textile wastes would increase visibility of and acknowledge the environmental degradation the current used textile trade causes the Global South. The principle of environmental justice, as an underlying principle of the Basel Convention, is used as a tool to analyse the implications of a textile amendment to the Convention. The thesis concludes that although the Basel Convention contains some environmental justice weaknesses, such as the ‘Repairables Loophole’ and the limited capacity for corrective justice, a textile amendment to the Basel Convention could at least partly further the concept of environmental justice. One key concern relating to the used textile trade is the distinction between textile waste and non-waste. Through technical guidance under the Basel regime, legal clarity on this distinction could be achieved. While legal clarity on this matter is important for an environmentally sound and just used textile trade, it does not guarantee that all environmental injustices of this issue are resolved. For example, field visits to illegal textile dumps show that even reusable textiles end up discarded in illegal dumps. The influential role of the EU in developing IEL is analysed in relation to a potential textile amendment to the Basel Convention. The EU has played a central role in the negotiations for other international environmental agreements. Given the Union’s leading role in the regulation of used textiles and the shared foundation of the WSR and the Basel Convention, the WSR is relatively well adapted to being incorporated into the Convention. However, the more limited scope of the Basel Convention may impede the merge of the two instruments. Furthermore, the trend of the EU setting the agenda for the development of IEL is problematic for procedural environmental justice. While a textile amendment to the Basel Convention has the potential to further environmental justice, procedurally unjust negotiations for the amendment would invalidate the potential progress for distributive justice. To ensure procedural justice, I advocate for increased attention paid toward issues such as waste minimisation and liability.
Keywords: folkrätt; public international law; environmental law; miljörätt; international environmental law; waste law